Practicing Principles of Moral Literary Criticism in the Poems (Sadness Market) - Hamed, Nimallah H. (Humanities Journal of University of Zakho, 2018)
Moral Criticism in literature is an approach for analyzing and evaluation literary texts in order to determine moral themes and clarify the application of these themes in literary texts. Apparently, this literary approach has emerged in Kurdish literary criticism as well. The main goal of this research is to find out the moral themes in the chosen collection of poems (sadness market) and analyzing them according to the main principles of this approach to find out to what extend the poet are succeeded in his moral messages, especially in the aspects of the leadership and directing. Furthermore, this research aims to refine the range of the moral attention and consciousness of the poet toward the individual in the society. Additionally, another aim of this research is to discover the creativity of the poet in terms of the guiding the readers toward the respectable mentalities. this is, definitely, approves the experiences of the poet. In conclusion, this critical approach is an effective method to evaluate and analyze literary texts. It can determine and study how the moral themes reflected in literary texts.